Pengaruh Strategi Konversi Peta Konsep Terhadap Retensi Mahasiswa Jurusan Pendidikan IPA Biologi Universitas Islam Negeri Mataram - Agustiningsih, Neneng (Jurnal Pendidikan Biologi, 2017)
This study aims to examine the effect of mind map conversion strategy toward students retention of Biology Education Department in UIN Mataram, year 2016-2017. This research is a Quasi Experiment, using non equivalent control group design with pretest âposttest which performed in two groups of the fourth semester students. Treatment group is class C used mind map conversion strategy, and as control group is class D used a multistrategy, with total of 63 students. The retention instrument uses a mind map scoring sheet. The retention hypothesis was analyzed using t-test by SPSS version 21. The statistical analysis showed sig.t test = 0,00 < 0,05 then H0 is rejected. This mind map conversion strategy has a significant influence toward the retention of class C students.